Contributing to the Supply Chain Management theory establishment - Crespo de Carvalho, J. (Economia Global e Gestão, 2011)
The purpose of this paper is to contribute to the development of the SCM theory and practice. First, by revisiting the theories and areas of knowledge that contributed to the emergence of SCM. Secondly, by establishing a set of statements – for discussion – that should constitute the basis of Supply Chain Management as an area of organizational and inter-organizational knowledge, able to create competitive advantages and to be foreseen as an idiosyncratic though pre-paradigmatic area of knowledge.